Pendampingan Akselerasi Baca Al-Qur’an Ibu Rumah Tangga Buta Huruf Hijaiyah di Desa Sukoharjo Plemahan Kediri - Akbar, Fadhil; Wahyudin, Aji (Proceedings of Annual Conference on Community Engagement, 2022)
The condition of the social environment has recently been heavily influenced by social media, as well as the reduced Islamic values ​​in the Sukoharjo Plemahan Kediri community, especially with regard to reading the verses of the Qur'an in prayer. This program focuses on fostering reading the Qur'an for housewives who are illiterate hijaiyah. By using the Participatory Action Research method, it is hoped that these Qur'an reading skills will increase. The goal is that people who are illiterate hijaiyah can read verses of the Qur'an in accordance with the rules of writing good and correct Arabic, and are able to understand the Qur'an well. Housewives who previously had not been able to read hijaiyah letters properly and according to the rules of tajwid and makhroj within one month they were able to master reading the Qur'an well and fluently.